Decreased Post-Cesarean Endometritis Following Povidone Iodine-Vaginal Preparation - Alaa Raheem Kareem; Wasan Munim; Niran Kamel; Mustafa Rasool Aal- Saleh; Sarah Abdulkareem Ali Al-Dujaili; Mohammed Luay Subhi (Diyala Journal of Medicine, 2020)
Background: Despite the use of several strategies to prevent post-Cesarean complications including wound infections and endometritis, they remain high morbidities.